Insect Management for Sweet Potatoes - Susan E. Webb (EDIS, 2002)
This document is ENY-473 (which replaces ENY-443), one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2001. Revised: July 2002.